The Psychological Dynamics of Victims of Domestic Violence: A Phenomenological Study from the Perspectives of Social Pathology and Islamic Guidance and Counseling - Nur Syifa Latifah; Nor Fatmah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Domestic violence is a form of social pathology that continues to occur frequently in modern society. Domestic violence not only causes physical harm but also has significant effects on the psychological condition of victims. This study aims to understand the psychological experiences of domestic violence victims and the forms of intervention that can be provided through an Islamic Guidance and Counseling approach. This research employed a qualitative method with a phenomenological approach. The research subjects consisted of two women who were victims of domestic violence and experienced verbal and psychological abuse within their households. Data collection techniques included in-depth interviews and simple observations. The findings reveal that victims experienced psychological trauma, anxiety, low self-esteem, fear, and difficulties in building social relationships. In addition, victims tended to remain in abusive relationships due to factors related to children, economic dependence, and social pressure. The Islamic Guidance and Counseling approach, through emotional support, spiritual reinforcement, and individual counseling, assisted victims in the process of mental recovery. This study demonstrates that domestic violence is both a social and psychological problem that requires serious attention from families, communities, and counseling institutions.